J2ME-Based 2D Rubber Puzzle Mobile Game - Waliya Rahmawanti; Rogayah Rogayah; Nur Azizah (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
2D Rubix Game is part of an educational game. 2D Rubix Game in addition to being a medium of entertainment, is expected to help users sharpen their brains in managing strategy. 2D rubix game has 4 levels, where the higher the level, the more difficult and many rubix dimensions. 2D rubix game also has a new game menu, save, load game, and highscore. 2D Rubix Game created using the Java programming language with J2ME functions. J2ME is a part of the Java programming language that can be used to create applications for various electronic media. Rubix 2D game has conducted a trial process on the emulator and all menus can run according to their functions